Profile of Nutritional Status and Hemoglobin Levels among School-Aged Children in a Coastal Area of North Lombok - Rifana Cholidah; Ida Ayu Eka Widiastuti; Ima Arum Lestarini; Seto Priyambodo (Lembaga Publikasi Ilmiah Nusantara, 2026)
Anemia remains a significant public health problem among school-aged children in Indonesia. This study aimed to describe hemoglobin levels and nutritional status among primary school children in a coastal area of North Lombok. A descriptive cross-sectional study was conducted among 102 children aged 7–12 years from three elementary schools in Malaka Village, West Nusa Tenggara. Nutritional status was assessed using body mass index-for-age Z-scores, while hemoglobin levels were measured using a portable hemoglobin device. The results showed that 57.9% of children were anemic, including 16.7% with mild anemia and 41.2% with moderate anemia, while most children (72.5%) had a normal nutritional status. No severe anemia cases were identified. These findings suggest that anemia remains common despite predominantly normal anthropometric status among school-aged children in this coastal population.